Pengembangan Media Game Based Learning (GBL) Pada Pembelajaran Dasar Kuliner Siswa SMK Program Keahlian Kuliner Kelas X - Shellyna Fidya Silka; Sri Handajani; Niken Purwidiani; Asrul Bahar (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to determine: (1) the result of development of media GBL used in basic culinary learning class X, (2) feasibility of GBL media for basic culinary learning for class X culinary vocational students, (3) Vocational students’ responses to GBL media in basic culinary learning. This research method is R&D with Plomp development model with five stages (prelimenary investigation, design, realization, test;evaluation;and revision, implemented), but due to research limitations, this research was carried out until 4th stage. The media validation involved three material experts and three media experts. The research object is a wordwall game and students responses. The instruments used for the feasibility of the game include material validation, media, and questionnaires to see student responses. As for the technique of data analysis carried out quantitatively. The result showed: (1)the result of the media that had been made in from of a QR code that can be scanned by readers, (2) the result of material and media validation with an average value 77,86% and 88,94% included worth with a little revision and (3) student responses have an average score 89,05% with very good interpretation. This indicates that the development of wordwall game can be used in learning.